Calculus : for business, economics, and the social and life sciences - Hoffmann, Laurence D.; Bradley, Gerald L. (Boston : McGraw-Hill, 2000)
Mathematics and Statistics
Keywords: Calculus; Business; Economics; Social sciences; Life sciences; Differentiation; Optimization; Logarithm; Integration; Variables